Wheat–Fusarium graminearum Interactions Under Sitobion avenae Influence: From Nutrients and Hormone Signals - Luo, Kun; Ouellet, Thérèse; Zhao, Huiyan; Wang, Xiukang; Kang, Zhensheng (Frontiers in Nutrition, 2021)
Fusarium head blight (FHB) epidemics is caused by toxigenic cereal pathogens Fusarium graminearum and closely related species; its severity is potentially increased by preinfestation with wheat spike colonizer aphid Sitobion avenae. An important question is how to discover the ‘synergistic’ effects of the coexistence of S. avenae and F. graminearum on wheat spikes in agricultural ecosystems. In recent decades, extensive studies typically focused on unravelling more detail on the relationship between wheat–aphids and wheat–pathogens, which have greatly contributed to our understanding of this tripartite interactions at ecology level. Here we synthesize recent advances related to the tripartite interaction S. avenae–cereal–F. graminearum from the aspects of environmental nutrients and hormonal signals. We propose that the aphid honeydew excreted by S. avenae and their endosymbionts provide ready-to-use nutrients accelerating infection by the pathogen F. graminearum. Furthermore, F. graminearum infection is associated with accumulation of the growth phytohormone auxin, possibly interfering with hormone-dependent defense responses and stimulating the infected plants to release more nutrients. This review highlights the relevance of herbivore S. avenae pre-exposure to trigger the accumulation of mycotoxins production, which stimulates the infection process of F. graminearum and epidemic of FHB in natural ecosystems.